Clinical Aspects of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis With Severe Ocular Complications in South Korea - Kim, Mee Kum; Yoon, Kyung Chul; Yoon, Sook Hyun; Seo, Kyoung Yul (Frontiers in Medicine, 2021)
This review describes the current knowledge regarding genetic susceptibilities and treatment strategies for Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), with ocular complications, in Korea. In a case-control study, the gene frequencies of both HLA-A*0206 (20.0%) and HLA-Cw*0304 (15.0%) increased but the gene frequency of HLA-Cw*0303 (1.3%) decreased with cold medicine (CM)-SJS/TEN with severe ocular complications (SOCs). In a case-series, positive genotyping of HLA-B*5801 was 80.0% in allopurinol-induced SJS/TEN without SOCs. In a genome-wide association study, HLA-A*0206 was substantially related to CM-SJS/TEN with SOCs. Both HLA-A*0206 and prostaglandin-E receptor 3 (PTGER3) single nucleotide polymorphism (SNP) rs1327464 exert a synergistic effect on SOCs in CM-SJS/TEN. In the acute stage, conventional procedures, amniotic membrane transplantation or suture-less amniotic contact lenses are applied. Applications of intravenous Immunoglobulin (IVIG) or mega-dose steroids are attempted in patients with high acute ocular and systemic involvement scores. In the chronic stage, keratolimbal transplantation and penetrating keratoplasty are the standard procedures. Either autologous nasal or oral mucosal grafts, or biomaterial-free cultured oral mucosal epithelial cell sheets are transplanted as alternative therapies. Deep anterior lamellar keratoplasty is attempted. Combined photodynamic therapy with intrastromal bevacizumab injection or intense pulse laser are used to resolve chronic ocular complication. Corneoscleral contact lenses are available for a visual rehabilitation. As a last resort, Seoul-type keratoprosthesis had been transplanted. There are unmet needs to standardize nationwide ocular grading system and to correct tarsal scarring using mucosal grafting. This review provides a perspective on the current practices to treat ocular complications in SJS/TEN.